Managing disinflation under uncertainty - Mewael F. Tesfaselassie; Eric Schaling (Kiel Institute for the World Economy (IfW), 2008)
In this paper we analyze disinflation policy when a central bank has imperfect information about private sector inflation expectations but learns about them from economic outcomes, which are in part the result of the disinflation policy. The form of uncertainty is manifested as uncertainty about the effect of past disinflation policy on current output gap. Thus current as well as past policy actions matter for output gap determination. We derive the optimal policy under learning (DOP) and compare it two limiting cases—certainty equivalence policy (CEP) and cautionary policy (CP). It turns out that under the DOP inflation stay between the levels implied by the CEP and the CP. A novel result is that this holds irrespective of the initial level of inflation. Moreover, while at high levels of inherited inflation the DOP moves closer to the CEP, at low levels of inherited inflation the DOP resembles the CP. – Learning ; inflation expectations ; disinflation policy ; separation principle ; Kalman filter ; optimal control – In this paper we analyze disinflation policy when a central bank has imperfect information about private sector inflation expectations but learns about them from economic outcomes, which are in part the result of the disinflation policy. The form of uncertainty is manifested as uncertainty about the effect of past disinflation policy on current output gap. Thus current as well as past policy actions matter for output gap determination. We derive the optimal policy under learning (DOP) and compare it two limiting cases—certainty equivalence policy (CEP) and cautionary policy (CP). It turns out that under the DOP inflation stay between the levels implied by the CEP and the CP. A novel result is that this holds irrespective of the initial level of inflation. Moreover, while at high levels of inherited inflation the DOP moves closer to the CEP, at low levels of inherited inflation the DOP resembles the CP.
Keywords: E52; F33; C53; E43; C53; 330; Learning; Inflation Expectations; Disinflation Policy; Separation Principle; Kalman Filter; Optimal Control; Inflationsbekämpfung; Entscheidung bei Unsicherheit; Inflationserwartung; Lernprozess; Kontrolltheorie; Zustandsraummodell; Theorie